Effect of micro-segregation of alloying elements on the precipitation behaviour in laser surface engineered Alloy 718. (15th May 2021) - Mantri, Srinivas Aditya; Dasari, Sriswaroop; Sharma, Abhishek; Alam, Talukder; Pantawane, Mangesh V.; Pole, Mayur; Sharma, Shashank; Dahotre, Narendra B.; Banerjee, Rajarshi; Banerjee, Srikumar
Abstract: Laser surface engineering has been employed to mimic the microstructural evolution during laser-based additive manufacturing of Alloy 718, specifically when the layers are successively fused and solidified. The micro-segregation of alloying elements in the fusion zone of laser surface melted Alloy 718 samples has been found to have a strong influence on the local precipitation behavior. The dendritic structure produced by rapid melting and solidification has shown three distinct zones – a) the core and b) the periphery of dendrites, and c) the inter-dendritic channel. While precipitation of γ' [Ni3 (Al, Ti, Nb)] dominates in the core, the periphery is decorated by γ" [Ni3 (Nb, Mo)] and composite γ'/γ" precipitates, all in the austenite(γ) matrix. The inter-dendritic channel, rich in Nb, Mo, and C, contains discretized aggregates of Laves phase and carbides, which act as preferential nucleation sites for the equilibrium δ phase. The Nb enrichment in these channels also results in a high density of γ" precipitates on subsequent annealing. Microscopic examinations at different length scales using SEM, site specific TEM (both diffraction contrast and phase contrast) and Atom Probe Tomography (APT) have revealed several hitherto unknown features of precipitation processes in a compositionally inhomogeneous Alloy 718, which are invariably encountered in components produced by laser additive manufacturing. Results are rationalized in terms of quantitative elemental analyses, in nm scale, of micro-segregation of alloying elements in local regions by 3-D APT. Graphical Abstract: Image, graphical abstract